Building high quality databases for minority languages such as Galician - Campillo, F.; Braga, D.; Belén Mourin, A.; García-Mateo, C.; Silva, P.; Dias, M. S.; Méndez, F. (Proceedings of the 7th International Conference on Language Resources and Evaluation, LREC 2010, 2010)
This paper describes the result of a joint R&D project between Microsoft Portugal and the Signal Theory Group of the University of Vigo (Spain), where a set of language resources was developed with application to Text-to-Speech synthesis. First, a large Corpus of 10000 Galician sentences was designed and recorded by a professional female speaker. Second, a lexicon with phonetic and grammatical information of over 90000 entries was collected and reviewed manually by a linguist expert. And finally, these resources were used for a MOS (Mean Opinion Score) perceptual test to compare two state-of-the-art speech synthesizers of both groups, the one from Microsoft based on HMM, and the one from the University of Vigo based on unit selection.